Diaphragmatic Breathing Exercise in Children - Calmon, Cristina Maria Santos; Góes, David Luiz; Bermudez, Diana Guimarães de Oliveira; Gonçalves, Renata Maba; Castilho, Tayná; Schivinski, Camila Isabel Santos (Manual Therapy, Posturology & Rehabilitation Journal, 2016)
Introduction: Some studies conducted in adult and pediatric population, show the benefit of diaphragmatic breathing exercise for individuals with asthma, cystic fibrosis and even in cases of vertigo. Thus, this literature review paper aims to gather and present scientific evidence on the use of diaphragmatic breathing exercise as a therapeutic strategy in the children diseases. Objective: to present scientific evidence about diaphragmatic breathing exercise as in children’s affections. Method: Science Direct, MEDLINE, SciELO, Portal CAPES, PubMed and Bireme, considering the published articles from 1956 to 2016, searched through the descriptors Ciências da Saúde (DeCS):“physical therapy”, “pediatric”, “children”, “breathing” and “diaphragmatic breathing”. Was also consulted the bibliographic Universidade do Estado de Santa Catarina (UDESC). There was included the texts related to treatments and trials about diaphragmatic breathign exercise as a therapeutic strategy in pediatrics. Results: Were selected eleven journal articles and one dissertation of course compatible with the established criteria. Conclusions: The publications board the diaphragmatic breathing exercise in premature children, cystic fibrosis, asthma, mouth breathing syndrome, neuromuscular diseases, chronic functional constipation and dysfunctional voiding. Conclusion: This resource has presented positive results in some clinic situations, but are required more investigations about the effects of this therapeutic strategy in children.